59: EVIDENCE BASED DECISION MAKING ABOUT FACTORS AFFECTING CONSULTATION LENGTH OF PHYSICIANS WORLDWIDE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (8th February 2017) - HajEbrahimi, Sakineh; Janati, Ali; Hasanpoor, Edris; Arab-Zozani, Morteza; Sokhanvar, Mobin; Pashzadeh, Fariba; HaghGoshyie, Elaheh
Abstract : Background and aims: Consultation length is a crucial aspect of patient-physician interaction that its inadequacy can negatively influence the treatment and diagnosis efficiency. The purpose was to determine factors related to consultation length of physicians and we sought to compare consultation length in different countries worldwide. Methods: We searched PubMed, Web of Science, Cochrane, ProQuest, and Scopus. Also, we searched Google Scholar for finding of the entire articles that theses related to consultation length. We used data sources up to November, 2015, without language restriction and searched the reference lists of retrieved articles. We extracted Consultation length and Factors related to it and assessments for their methodological quality using the AXIS (Appraisal tool for Cross-Sectional Studies) checklist. Meta-analyses were conducted using Comprehensive Meta-Analysis Version (CMA) 2.0. We used a random-effects model for the meta-analyses of factors. Results: Of the 16 911 identified studies, 189 met full inclusion criteria. Of 189 studies assessed, 125 cases (67%) were conducted in USA, UK, Australia and Netherlands. Only, 49 (26%) studies were strong evidence. 164 (86.77%) studies were face to face consultations. The effect of three variables physicians' gender, patients' gender and type of consultation investigated on the consultation length. According to moderate and strong evidence, no statistically significant difference was found in the consultation length in female and male doctors (p=0.891). Also, no statistically significant difference was found in the consultation length between female and male patients (p=0.314) and telemedicine and face to face (p=0.170) visits. Conclusions: According to all evidence, The results showed that no association was identified between consultation length and three factors in the random-effects model. It seems patient-physician interaction more than studied variables, influence the length of consultations.